2015
DOI: 10.1586/14779072.2015.1002466
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gender gap in atrial fibrillation

Abstract: Women have a similar lifetime prevalence of non-valvular atrial fibrillation (NVAF) compared with that of men. Given the significant morbidity and potential mortality associated with NVAF, it is crucial to understand gender differences with NVAF. Women can be more symptomatic than men. Despite a higher baseline stroke risk, they are less likely to be on anticoagulation. Women have a greater risk of thromboembolism and a similar rate of bleeding risk compared with men on anticoagulation. Initial experience sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Cardioversion to normal sinus rhythm is equally successful in women and men; however, women were less likely to undergo electric cardioversion than men 29. In addition, women were less likely to undergo catheter ablation and, when this procedure is performed, they are older and with larger left atrial dimension 102,103…”
Section: Managementmentioning
confidence: 99%
“…Cardioversion to normal sinus rhythm is equally successful in women and men; however, women were less likely to undergo electric cardioversion than men 29. In addition, women were less likely to undergo catheter ablation and, when this procedure is performed, they are older and with larger left atrial dimension 102,103…”
Section: Managementmentioning
confidence: 99%
“…Women have a higher age of AF onset, a greater risk of embolic stroke, a poorer quality of life, a higher heart rate during AF, more adverse effects to antiarrhythmic drugs, a different pattern of AF trigger localisation and differences in how the autonomic nerve system modulates cardiac electrophysiology 6. Thus, it is reasonable to assume that also the cardiac response to physical activity may differ between the genders.…”
Section: Is There a Gender Difference In The Effects Of Physical Actimentioning
confidence: 99%
“…However, the US Government Accountability Office performed an assessment of adverse events by sex and reported that 8 of 10 drugs removed from the market by the FDA were because of adverse events in women . Males and females have dissimilar health issues, metabolize and react to some drugs differently, respond to medical devices differently, and can have diverse outcomes after medical interventions …”
Section: Introductionmentioning
confidence: 99%